Propuesta arquitectónica de vivienda sostenible a través de la tectónica del lugar Caso de estudio; comunidad de Pulingui, cantón Guano. - Soque Guaman, Lizeth Valeria (2026)
This research develops a sustainable housing proposal through the tectonics of place, addressing the social, environmental, and constructional challenges facing the community of Pulingui in the canton of Guano, where a significant housing deficit persists. The main objective is to design a sustainable and progressive rural dwelling that adapts to local environmental conditions, responds to community housing needs, and optimizes the use of locally available resources. The architectural proposal demonstrates how place-based design can advance sustainability in rural housing construction. The research employs site analysis, local material studies, ethnographic investigation of inhabitation patterns, and spatial configuration analysis, using methodological tools such as analysis sheets and community surveys. The findings validate the potential of traditional earth-based construction systems— particularly adobe and rammed earth—while demonstrating that these systems achieve optimal performance when integrated with contemporary construction techniques, modern materials, and bioclimatic design strategies. The architectural proposal indicates that integrating the tectonics of place with bioclimatic strategies in housing design yields a sustainable architecture that effectively responds to both the natural environment and the rural context. This place-based approach not only addresses environmental sustainability but also enhances residents' quality of life by creating dwellings that are culturally resonant, climate-responsive, and economically viable.